Women endurance runners with menstrual dysfunction have prolonged interruption of training due to injury - Beckvid Henriksson, G.; Schnell, C.; Linden Hirschberg, A. (Gynecology and obstetric investigation, 2000)
Strenuous exercise by women is associated with menstrual dysfunction, eating disorders and osteoporosis. Intensive training may also increase the susceptibility to infections. In this study, we investigated whether menstrual dysfunction was related to musculoskeletal injuries and/or upper respiratory tract infections in women middle/long-distance runners. A questionnaire was mailed to 127 Swedish female runners of whom 75% answered. This retrospective study showed a higher frequency of menstrual disorders (25%) in runners than in the general population. Furthermore, almost half of the athletes (46%) were classified as at risk of developing eating disorders. Women athletes with menstrual dysfunction were found to have had a longer interruption of training due to musculoskeletal injuries than those with regular cycles (34.1 +/- 3.0 vs. 9.0 +/- 9. 4 days, p < 0.05). However, no relation was found between susceptibility to infections and menstrual status.